2018
DOI: 10.1101/405498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing genomic admixture between cryptic Plutella moth species following secondary contact

Abstract: Cryptic species are genetically distinct taxa without obvious variation in morphology and are occasionally discovered using molecular or sequence datasets of populations previously thought to be a single species. The world-wide Brassica pest, Plutella xylostella (diamondback moth), has been a problematic insect in Australia since 1882, yet a morphologically cryptic species with apparent endemism (P. australiana) was only recognized in 2013. Plutella xylostella and P. australiana are able to hybridize under lab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…The gene branching order indicated that the initial SulfC duplication, resulting in GSS3 and GSS1/2 , occurred early in the Plutella lineage, whereas the subsequent duplication of GSS1/2 , leading to PxGSS1 and PxGSS2 , likely took place after the P. xylostella and P. australiana lineages diverged from a common ancestorabout two Ma (Ward and Baxter 2018). Because all three GSS genes in the DBM genome, PxGSS1 , PxGSS2 , and PxGSS3 , coded for enzymes with GSS activity, we deduced that this activity had emerged before SulfC duplicated in the Plutella lineage.…”
Section: Resultsmentioning
confidence: 99%
“…The gene branching order indicated that the initial SulfC duplication, resulting in GSS3 and GSS1/2 , occurred early in the Plutella lineage, whereas the subsequent duplication of GSS1/2 , leading to PxGSS1 and PxGSS2 , likely took place after the P. xylostella and P. australiana lineages diverged from a common ancestorabout two Ma (Ward and Baxter 2018). Because all three GSS genes in the DBM genome, PxGSS1 , PxGSS2 , and PxGSS3 , coded for enzymes with GSS activity, we deduced that this activity had emerged before SulfC duplicated in the Plutella lineage.…”
Section: Resultsmentioning
confidence: 99%
“…Although these species can hybridize in laboratory crosses, whether hybridization occurs in the wild is unknown 35 . Whole genome analysis of 29 Plutella individuals found no evidence for widespread introgression between these two species 59 . In our study, all Esperance and Southend individuals exhibited levels of heterozygosity across > 550,000 variant and invariant genome-wide loci that were similar to other P. xylostella .…”
Section: Discussionmentioning
confidence: 91%
“…No potential conflicts of interest are reported by the authors. (Chen, Jiang, et al 2019); Gibbovalva kobusi, MK956103 (Chen, Liao, et al 2019); Phyllocnistis citrella, MN792920 (Liu et al 2020); Corythoxestis sunosei, MT611524 (Zhang et al 2020); Plutella xylostella, JF911819 and KM023645 (Wei et al 2013;Dai et al 2016); Plutella australiana, MG787473 (Wardz and Baxter 2018); Leucoptera malifoliella, JN790955 (Wu et al 2012); Lyonetia clerkella, MF045483 (Unpublished); Prays oleae, KM874804 (van Asch et al 2016); Astrotischeria sp., KJ508056 (Timmermans et al 2014); Stigmella roborella, KJ508054 (Timmermans et al 2014).…”
Section: Disclosure Statementmentioning
confidence: 99%
“…and Stigmella roborella) were included as an outgroup. GenBank accession numbers of the species analyzed are as follows: Amorophaga japonica, MH823253 (Kim et al 2020); Tineola bisselliella, KJ508045 (Timmermans et al 2014); Eumeta variegata, MH574939 (Jeong et al 2018); Mahasena colona, KY856825 (Li et al 2017); Dahlica ochrostigma, MK890245 (Roh et al 2019); Acanthopsyche nigraplaga, MT883999 (Lee et al 2021); Eudarcia gwangneungensis, MN413148 (Roh et al 2020); Phyllonorycter froelichiella, KJ508048 (Timmermans et al 2014); Phyllonorycter platani, KJ508044(Timmermans et al 2014); Cameraria ohridella, KJ508042(Timmermans et al 2014); Caloptilia theivora, MK541932(Chen, Jiang, et al 2019); Gibbovalva kobusi, MK956103(Chen, Liao, et al 2019); Phyllocnistis citrella, MN792920(Liu et al 2020); Corythoxestis sunosei, MT611524(Zhang et al 2020); Plutella xylostella, JF911819 and KM023645(Wei et al 2013;Dai et al 2016); Plutella australiana, MG787473(Wardz and Baxter 2018); Leucoptera malifoliella, JN790955(Wu et al 2012); Lyonetia clerkella, MF045483 (Unpublished); Prays oleae, KM874804 (van Asch et al 2016); Astrotischeria sp., KJ508056(Timmermans et al 2014); Stigmella roborella, KJ508054(Timmermans et al 2014).…”
mentioning
confidence: 99%